PERKOSAAN DAN MEKANISME KOLONIALISASI JENDER - Siti Ruhaini Dzuhayatin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
Rape is not a new phenomenon in the human history, and is continuously regarded as a tragic social issue. Rape as the mechanism of domination and control has been exercised by great nations in the past. Rape perpetually furnishes the international agenda from the Universal Declaration of Human Rights to the latest conference on Violence Against Women in Valencia, Spain on November, 24-26, 2000. The conference stipulates that rape is the violation against humanity which put women as the victims.The paper will focuse on how rape has been used as the means of domination and control of women, either individually and collectively. The paper will also explore theframeworks which illustrate rape as the means of domination which is parallel to colonialization. pinally, the paper will show the shifting paradigm from rape as 'man to man' issues to women rights issues. Women's struggle to affirm rape as human rights violation has made a significant progress by the establishment of The International Tribunal on mass rape as a crime against humanity.